2015
DOI: 10.1080/17461391.2015.1111939
|View full text |Cite
|
Sign up to set email alerts
|

Exercise promotes IL‐6 release from legs in older men with minor response to unilateral immobilization

Abstract: Physical inactivity is a major contributor to low-grade systemic inflammation. Most of the studies characterizing interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α) release from exercising legs have been done in young, healthy men, but studies on inactivity in older people are lacking. The impact of 14 days of one-leg immobilization (IM) on IL-6 and TNF-α release during exercise in comparison to the contralateral control (CON) leg was investigated. Fifteen healthy men (age 68.1 ± 1.1 year (mean ± SEM); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Despite this, we observed no exercise-induced cytokine responses to exercise. These findings support the suggestion that acute cytokine responses to exercise may be blunted in older adults (Hamada et al, 2005 ; Reihmane et al, 2016 ) compared to previous observations in younger adults (Reihmane et al, 2013 ). Further studies comparing acute cytokine responses to short-term exercise in older and younger participant groups would help further clarify the effect of age on the inflammatory response to exercise.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Despite this, we observed no exercise-induced cytokine responses to exercise. These findings support the suggestion that acute cytokine responses to exercise may be blunted in older adults (Hamada et al, 2005 ; Reihmane et al, 2016 ) compared to previous observations in younger adults (Reihmane et al, 2013 ). Further studies comparing acute cytokine responses to short-term exercise in older and younger participant groups would help further clarify the effect of age on the inflammatory response to exercise.…”
Section: Discussionsupporting
confidence: 90%
“…The current study is the first to compare acute cytokine responses to exercise in participants with above average (37.4 ± 5.9 mL.kg −1 .min −1 ) and below average (22.6 ± 2.8 mL.kg −1 .min −1 ) cardiorespiratory fitness levels, relative to age-specific normative data (Stensvold et al, 2017 ). Our findings indicate that the blunted cytokine response to exercise previously reported among older adults (Hamada et al, 2005 ; Reihmane et al, 2016 ) is not likely to be due to low fitness levels.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Because of a minor influence of systemic factors that could potentially influence muscle atrophy (122), leg immobilization represents a suitable model to study muscle loss caused by isolated disuse per se. In contrast, with the use of the bed rest model, muscle loss is possibly influenced by systemic factors that are activated due to whole body disuse.…”
Section: Models Of Muscle Disuse Atrophymentioning
confidence: 99%
“…Accordingly, the IL-6 release from working muscles after 60 min of workout is preserved in healthy, 70-year-old men (83) when a two-leg knee extensor exercise is performed without muscle damage. Reihmane et al (84) reported that 45 min of two-leg dynamic knee extensor exercise at 19.5 ± 0.9 W increases IL-6 release from rest to 30 min of exercise but was not higher than the resting level after 45 min of exercise. In addition, after isokinetic exercise, the expression of MCP-1, IL-8 and IL-6 (pro-inflammatory) increased substantially while, the expression of the antiinflammatory cytokines IL-4, IL28 and IL-13 increased only slightly (or not at all) after exercise (85).…”
Section: Cytokine and Myokine Serum Production And Release During Exercisementioning
confidence: 97%